Secure Routing Protocol for WSNs Using Bacterial Foraging Optimization and Improved RC4 (Informatica, 2022)
Wireless sensor networks (WSNs) have recently received important sponsorship in various fields, such as medical treatment, emergency response, environmental monitoring, military monitoring, outer space research, etc. Sensor nodes are usually limited in capabilities, including batteries. These networks can handle critical data in hostile and uncontrolled environments. Sensor nodes are deployed in harsh, hazardous, or hard-to-reach environments, making it difficult to replace or recharge these batteries, so it is important to consider the security and energy consumption issues when designing such networks. Therefore, this paper proposed a new secure and energy-efficient routing protocol called Improved RC4 with Bacterial Foraging Optimization Routing Protocol (IRC4-BFORP) for WSNs. IRC4 has represented the improvement of RC4 to make the original algorithm safer and faster. The IRC4 is used to secure the sensing data sensed by the sensors before sending it to the sink. To demonstrate the effectiveness of IRC4 over the original algorithm, some numerical analyses are achieved. The results have shown that IRC4 is more secure than the original algorithm. Also, the BFORP has proposed to send the secure sensing data to the sink by selecting the preferred nodes in the transmission paths. The simulation results prove the effectiveness of the BFORP in reducing energy use and reducing delays on the one hand, compared with the well-known protocols that are used in routing.